2008
DOI: 10.5735/086.045.0102
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variation in Metric Asymmetry in Skulls of Polar Bears (Ursus maritimus) from East Greenland and Svalbard

Abstract: Fluctuating asymmetry (FA) as a measure of environmental stress was studied in polar bear (Ursus maritimus) skulls from East Greenland (n = 300, collected 1892-2004) and Svalbard (n = 391, collected 1950-2004). Nine metric traits in skull and lower jaw were measured. FA levels of each trait were compared between sex/age groups (subadults, adult females, adult males), periods (≤ 1960, > 1960), and localities (East Greenland, Svalbard). The period ≤ 1960 was chosen to represent a period prior to the appearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 75 publications
0
13
1
Order By: Relevance
“…Satellite telemetry studies and movement of marked animals have also indicated that polar bears range widely along the coast of eastern Greenland and in the pack ice in the Greenland Sea and Fram Strait (Born et al 1997; Wiig et al 2003), and that the exchange between East Greenland and the Barents Sea population is minimal (Wiig 1995; Born et al 1997; Wiig et al 2003). Separate populations (East Greenland/Barents Sea) was further supported by Henrichsen and Sjøvold (in: IUCN PBSG 1986), Sonne et al (2007b), and Bechshøft et al (2008a, 2008b, 2008c). However, recent satellite telemetry results indicate that home ranges of bears from the East Greenland population overlap with those of bears from the Fram Strait (Born et al 2009).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Satellite telemetry studies and movement of marked animals have also indicated that polar bears range widely along the coast of eastern Greenland and in the pack ice in the Greenland Sea and Fram Strait (Born et al 1997; Wiig et al 2003), and that the exchange between East Greenland and the Barents Sea population is minimal (Wiig 1995; Born et al 1997; Wiig et al 2003). Separate populations (East Greenland/Barents Sea) was further supported by Henrichsen and Sjøvold (in: IUCN PBSG 1986), Sonne et al (2007b), and Bechshøft et al (2008a, 2008b, 2008c). However, recent satellite telemetry results indicate that home ranges of bears from the East Greenland population overlap with those of bears from the Fram Strait (Born et al 2009).…”
Section: Discussionmentioning
confidence: 67%
“…Male bears were categorized as adults at the age of ≥ 6 years, and female bears at the age of ≥ 5 years (Rosing‐Asvid et al 2002). In a few instances the sex of individual bears was determined using the canonical discriminant functions given in Bechshøft et al (2008b). All animals were born ≤ 1960, as determined from age and date of capture (year of kill).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher levels of FA have been connected with increased population density , social stress , Gibbs & Breuker 2006, sexual selection (Mazzi et al 2003, Voigt et al 2005, nutritional stress (Pravosudov & Kitaysky 2006), heat stress (Siegel et al 1977, Petavy et al 2006, disease and parasitic stress (Møller 2006), and genetic factors such as increased levels of hybridization and (Borrell et al 2004, Andersen et al 2006. FA studies have been conducted on metric and meristic traits of a multitude of organisms (Zakharov & Yablokov 1990, Blagojevic & Vujosevic 2004, Vilisics et al 2005, Andersen et al 2006, Green & Lochmann 2006, Pelabon et al 2006, Bechshøft et al 2008.…”
Section: Introductionmentioning
confidence: 99%